2012
DOI: 10.1111/j.1574-695x.2012.00955.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of FimA inPorphyromonas gingivalisgenotype IV

Abstract: It has been reported that a large majority of periodontitis patients carry organisms with either type II or IV‐fimA, while type I is the most prevalent fimA genotype among Porphyromonas gingivalis‐positive healthy adults. Here we report characterization of recombinant fimbrial protein (rFimA) produced in Escherichia coli from genotype IV‐fimA. In SDS‐PAGE and immunoblot analysis after partial dissociation, type IV‐rFimA showed a ladder‐like pattern representing oligomeric/polymeric forms of native fimbrial str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Our negative control strain YPF1, a 33277 fimA deletion mutant, as expected, was devoid of detectable amounts of FimA. We were unable to detect FimA IV protein from strain W83 (IV), which is not surprising, as previous reports have shown that levels of expression are low in the this strain, and it is antigenically distinct from the type I protein, thus less reactive with FimA I antibody [54], [55]. Interestingly, while expression of FimA IV protein in strain W83 was undetectable, allelic exchange mutant A4 produced detectable amounts of FimA IV protein, implying that much higher levels of this protein are being expressed in the 33277 background than in the W83 background.…”
Section: Resultssupporting
confidence: 66%
“…Our negative control strain YPF1, a 33277 fimA deletion mutant, as expected, was devoid of detectable amounts of FimA. We were unable to detect FimA IV protein from strain W83 (IV), which is not surprising, as previous reports have shown that levels of expression are low in the this strain, and it is antigenically distinct from the type I protein, thus less reactive with FimA I antibody [54], [55]. Interestingly, while expression of FimA IV protein in strain W83 was undetectable, allelic exchange mutant A4 produced detectable amounts of FimA IV protein, implying that much higher levels of this protein are being expressed in the 33277 background than in the W83 background.…”
Section: Resultssupporting
confidence: 66%
“…Pili (or fimbriae) are filamentous structures on the bacterial cell surface, with crucial role in virulence and host cell attachment (Yoshimura et al, 2009;Ellison et al, 2022). The pathogenic role of type IV pilins has been reported for the periodontitis associated bacteria P. gingivalis (Choi et al, 2012) and Eikenella corrodens (Hood and Hirschberg, 1995), and their enhanced expression under periodontal disease conditions has been previously reported (Szafrański et al, 2015). Transcription of flagellin from Treponema was also enhanced in periodontal disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that P. gingivalis fimbriae are highly immunogenic and immunization with purified fimbria from P. gingivalis 381 inhibits the progression of periodontal disease. 37 Fimbriae are responsible for the adhesion and invasion of bacteria that can cause periodontal tissue damage. Some researchers have made it a vaccine candidate, because of its ability to facilitate adhesion and invasion of bacteria into tissues.…”
Section: Discussionmentioning
confidence: 99%